2004
DOI: 10.1152/jn.00205.2004
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 Adrenoceptor Agonists Generate a “Fast” NMDA Receptor-Independent Motor Rhythm in the Neonatal Rat Spinal Cord

Abstract: Noradrenaline, a potent activator of rhythmogenic networks in adult mammals has not been reported to produce functional rhythmic patterns in isolated spinal cords of newborn rats. We now show that a "fast" (cycle time: 1-4 s) transient rhythm was induced in sacrococcygeal (SC) and rostral-lumbar spinal segments of the neonatal rat by bath-applied noradrenaline. The fast rhythm was blocked by 1 microM of the alpha1-adrenoceptor antagonist prazosin but not by 1-20 microM of the alpha2-adrenoceptor blocker yohimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Recent clinical studies have shown that reactivation of the CPGs in spinal cord injury patients by afferent input is possible, and that it improves the motor function and mobility of patients with incomplete thoracic spinal injury (Wernig et al, 1995;Colombo et al, 2001;Dietz et al, 2002;Dietz and Harkema, 2004;Dietz, 2009). Our findings that stimulation of sacrocaudal afferents (SCAs) in the isolated spinal cord of the neonatal rat is a potent activator of the pattern generating circuitry in the sacral and limb moving segments Delvolvé et al, 2001;Strauss and Lev-Tov, 2003;Gabbay and Lev-Tov, 2004;Blivis et al, 2007; also see Whelan et al, 2000, for the neonatal mouse) enable us to use this preparation to study the functional organization and mechanism of action of the pathways that are involved in sensory-activation of the CPGs, under controlled in vitro conditions. Our previous work revealed that the SCA-induced rhythm is not generated by direct contacts between the stimulated afferents and the hindlimb CPGs, but that it involves synaptic activation of sacral neurons whose axons project to the hindlimb innervating segments of the spinal cord through the white matter funiculi (Strauss and Lev-Tov, 2003;Lev-Tov and O'Donovan, 2009;Lev-Tov et al, 2010).…”
Section: Introductionmentioning
confidence: 61%
“…Recent clinical studies have shown that reactivation of the CPGs in spinal cord injury patients by afferent input is possible, and that it improves the motor function and mobility of patients with incomplete thoracic spinal injury (Wernig et al, 1995;Colombo et al, 2001;Dietz et al, 2002;Dietz and Harkema, 2004;Dietz, 2009). Our findings that stimulation of sacrocaudal afferents (SCAs) in the isolated spinal cord of the neonatal rat is a potent activator of the pattern generating circuitry in the sacral and limb moving segments Delvolvé et al, 2001;Strauss and Lev-Tov, 2003;Gabbay and Lev-Tov, 2004;Blivis et al, 2007; also see Whelan et al, 2000, for the neonatal mouse) enable us to use this preparation to study the functional organization and mechanism of action of the pathways that are involved in sensory-activation of the CPGs, under controlled in vitro conditions. Our previous work revealed that the SCA-induced rhythm is not generated by direct contacts between the stimulated afferents and the hindlimb CPGs, but that it involves synaptic activation of sacral neurons whose axons project to the hindlimb innervating segments of the spinal cord through the white matter funiculi (Strauss and Lev-Tov, 2003;Lev-Tov and O'Donovan, 2009;Lev-Tov et al, 2010).…”
Section: Introductionmentioning
confidence: 61%
“…The bath-applied NA induced fast rhythms, which mimicked locomotor activity of the spinal cord in rostro-lumbar and sacrococcygeal, but not in caudal lumbar segments. 33 All these data point to segmentally differentiated capability of spinal networks in generation of locomotor activity, but they also stress an importance of the network in the rostral lumbar segments in the control of locomotion. Our results speak in favor of the latter as long-lasting, moderate locomotor exercise allowed revealing the neurochemical differences between these two parts of the lumbar spinal cord in the adult rat, which may reflect different regulatory mechanisms of the enzymes, which maintain the appropriate levels of neurotransmitters for a long-term function.…”
Section: Discussionmentioning
confidence: 95%
“…10,32 Several other lines of evidence indicate that in the neonatal rat, the network of interconnected spinal interneurons, which are capable of generating locomotor-like activity, located in the rostral lumbar segments shows greater capacity for rhythmicity than that in other segments. 13,14,28 Noteworthy, Gabbay and Lev-Tov 33 showed that in early developmental period not only rostral lumbar but also sacrococcygeal segments responded differently to NA than to caudal lumbar segments. The bath-applied NA induced fast rhythms, which mimicked locomotor activity of the spinal cord in rostro-lumbar and sacrococcygeal, but not in caudal lumbar segments.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the effects of genetic manipulations of known groups of spinal neurons on the function of the locomotor rhythm generator have been assayed by monitoring the motor pattern recorded from spinal neurons and the lumbar ventral roots (Gosgnach et al 2006;; see also reviews by Kiehn 2006;Lev-Tov and O'Donovan 2007). This approach offers great promise for dissecting the internal structure of the generator.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative analysis of rhythmic patterns produced by the spinal cord is traditionally focused on the frequency and the phase relation between the activities of populations of neurons. The quantitative data are usually extracted from the low-pass filtered or the integrated envelope of rectified rhythmic bursts either manually or semimanually using a computer-based detection of rhythmic waveforms (see Gosgnach et al 2006;). This type of analysis has several inherent problems: it is inaccurate especially when the signals are attenuated after pharmacological treatments, specific lesions, or genetic manipulations and it does not provide quantitative information about the power of the signal or the precise strength of coupling between populations of neurons.…”
Section: Introductionmentioning
confidence: 99%